Formation of orally fast dissolving fibers containing propolis by electrospinning technique - Asawahame,C. (Chiang Mai University, 2015)
© 2015 Chiang Mai University. All rights reserved. The objective of this study was to prepare orally fast dissolving fibers using the electrospinning process with hydrophilic polymers. Polyvinyl pyrrolidone (PVP) and polyvinyl alcohol (PVA) were chosen as the fiber-forming polymers and propolis was used as the active ingredient for antibacterial property in the fibers. Morphology of electrospun fibers was influenced by solution parameters (viscosity, conductivity, surface tension) and process parameters (electric field strength, flow rate, collector type). This investigation used different types and molecular weights of polymers (PVP K90, PVP K30, PVA MW 85,000-146,000 and PVA MW 47,000) to influence the spinnability of the polymer solution and so the morphology of the electrospun fibers. It was found that PVP K90 at 8–10% (w/v) in ethanol and PVA MW 85,000-146,000 at 10% (w/v) in deionized water produced electrospun fibers with appropriated quality and stability. Ethanol and deionized water were used as a mixed solvent to study the effect of co-solvent on fiber morphology. The results showed that increasing another solvent in the polymer solution changed the morphology of electrospun fibers and affected the stability of electrospun fibers. Incorporated propolis (2% w/v) and small amount of additives into PVP K90 (8% and 10% w/v)nanospun fibers gave smooth and uniform fiber morphology with diameters ranging from0.55-0.95 mm and produced fiber mats which wetted and dissolved rapidlyin water within 10 seconds.